2012
DOI: 10.1080/00140139.2012.703698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aircraft cabin noise on passenger comfort

Abstract: To improve passenger comfort in the aircraft with respect to cabin noise, passengers' reactions to specific noise conditions were systematically investigated. Two laboratory studies showed significant dose-response relationships between sound pressure level and subjective comfort ratings which differed due to the noise at specific seat positions in the aircraft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…-the impact of airline service quality and comfort on passenger choices (Balcombe, Fraser, & Harris, 2009;Jiang, 2013;Martin, Roman, & Espino, 2008;Park, Robertson, & Wu, 2004;Park, Robertson, & Wu, 2004Wojahn, 2002;Jiang, 2012;Pennig, Quehl, & Rolny, 2012;Wojahn, 2002;Yang, Hsieh, Li, & Yang, 2012;Zhang Y., Zhang, 2012); -the attributes of the airline service quality (Babbar & Koufteros, 2008;Curry & Gao, 2012;De Jager, Van Zyl, & Toriola, 2012;Kim & Lee, 2009;Martin, Roman, & Espino, 2011;Wen & Yeh, 2010) and the customer-value drivers (Boetsch, Bieger, & Wittmer, 2011;Park, Robertson, & Wu, 2009); -the evaluation of airline service quality (Chen & Chang, 2005;Cheng & Chang, 2006;Chou, Liu, Huang, Yih, & Han, 2011;Higgins, Lawphongpanich, Mahoney, & Yin, 2008;Liou & Tzeng, 2007;Pakdil & Aydin, 2007;Tsaur, Chang, & Yen, 2002); -the effect of service quality on airlines' performance (Sim, Koh, & Shetty, 2006), the proposal of methods and strategies for improving airline service quality (Liou, Tsai, Lin, & Tzeng, 2011;Liou, Yen, & Tzeng, 2010;Maji, 2012);…”
Section: A Model Model For Aircraft Evaluation Aircraft Evaluation Tomentioning
confidence: 99%
“…-the impact of airline service quality and comfort on passenger choices (Balcombe, Fraser, & Harris, 2009;Jiang, 2013;Martin, Roman, & Espino, 2008;Park, Robertson, & Wu, 2004;Park, Robertson, & Wu, 2004Wojahn, 2002;Jiang, 2012;Pennig, Quehl, & Rolny, 2012;Wojahn, 2002;Yang, Hsieh, Li, & Yang, 2012;Zhang Y., Zhang, 2012); -the attributes of the airline service quality (Babbar & Koufteros, 2008;Curry & Gao, 2012;De Jager, Van Zyl, & Toriola, 2012;Kim & Lee, 2009;Martin, Roman, & Espino, 2011;Wen & Yeh, 2010) and the customer-value drivers (Boetsch, Bieger, & Wittmer, 2011;Park, Robertson, & Wu, 2009); -the evaluation of airline service quality (Chen & Chang, 2005;Cheng & Chang, 2006;Chou, Liu, Huang, Yih, & Han, 2011;Higgins, Lawphongpanich, Mahoney, & Yin, 2008;Liou & Tzeng, 2007;Pakdil & Aydin, 2007;Tsaur, Chang, & Yen, 2002); -the effect of service quality on airlines' performance (Sim, Koh, & Shetty, 2006), the proposal of methods and strategies for improving airline service quality (Liou, Tsai, Lin, & Tzeng, 2011;Liou, Yen, & Tzeng, 2010;Maji, 2012);…”
Section: A Model Model For Aircraft Evaluation Aircraft Evaluation Tomentioning
confidence: 99%
“…Overall satisfaction usually includes the evaluation of thermal comfort, sound comfort, air quality, etc. Some studies have shown that noise has the largest impact on overall satisfaction of all factors [62][63][64][65]. So the influence of noise on human beings' comfort should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mellert et al (2008) found that when the sound level increased during a flight, the crew was more aware of symptoms such as tiredness, difficulty concentrating, swollen feet, and headaches; by contrast, awareness of these symptoms was lowered when the noise level decreased. Besides Mellert et al (2008), Pennig, Quehl, and Rolny (2012) also examined the effect of sound pressure levels (SPL) between 66 and 78 dB(A) on passengers’ comfort experience and positive mood in the aircraft cabin. They suggest that aircraft interior noise could be optimized by reducing the SPL and high-frequency components (sounds described as “shrill” and “bright”), and reducing “irregular” sounds.…”
Section: Research Questionsmentioning
confidence: 99%